The City, the River, the Bridge : Before and after the Minneapolis Bridge Collapse - Nunnally, Patrick (Book collections on Project MUSE., 2011)
On August 1, 2007, just after 6:00 p.m., during the evening rush hour in Minneapolis, the 1,900-foot-long, eight-lane I-35W bridge buckled and crashed into the Mississippi River. The unimaginable had happened right on the doorstep of the University of Minnesota Twin Cities campus. Many of the first responders were from the University, persevering in the midst of chaos and disbelief. In the ensuing weeks, research and engineering teams from the University reviewed the wreckage, searched for causes, and began planning for the future. The City, the River, the Bridge represents another set of resp.